Degludec hospital trial: A randomized controlled trial comparing insulin degludec U100 and glargine U100 for the inpatient management of patients with type 2 diabetes. Issue 1 (24th September 2021) - Galindo, Rodolfo J.; Pasquel, Francisco J.; Vellanki, Priyathama; Alicic, Radica; Lam, David W.; Fayfman, Maya; Migdal, Alexandra L.; Davis, Georgia M.; Cardona, Saumeth; Urrutia, Maria A.; Perez‐Guzman, Citlalli; Zamudio‐Coronado, Karla Walkiria; et al.
Abstract: Aims: Limited data exist about the use of insulin degludec in the hospital. This multicentre, non‐inferiority, open‐label, prospective randomized trial compared the safety and efficacy of insulin degludec‐U100 and glargine‐U100 for the management of hospitalized patients with type 2 diabetes. Methods: In total, 180 general medical and surgical patients with an admission blood glucose (BG) between 7.8 and 22.2 mmol/L, treated with oral agents or insulin before hospitalization were randomly allocated (1:1) to a basal‐bolus regimen using degludec (n = 92) or glargine (n = 88), as basal and aspart before meals. Insulin dose was adjusted daily to a target BG between 3.9 and 10.0 mmol/L. The primary endpoint was the difference in mean hospital daily BG between groups. Results: Overall, the randomization BG was 12.2 ± 2.9 mmol/L and glycated haemoglobin 84 mmol/mol (9.8% ± 2.0%). There were no differences in mean daily BG (10.0 ± 2.1 vs. 10.0 ± 2.5 mmol/L, p = .9), proportion of BG in target range (54·5% ± 29% vs. 55·3% ± 28%, p = .85), basal insulin (29.6 ± 13 vs. 30.4 ± 18 units/day, p = .85), length of stay [median (IQR): 6.7 (4.7‐10.5) vs. 7.5 (4.7‐11.6) days, p = .61], hospital complications (23% vs. 23%, p = .95) between treatment groups. There were no differences in the proportion of patients with BG <3.9 mmol/L (17% vs. 19%, p = .75) or <3.0 mmol/L (3.7% vs. 1.3%, p = .62) between degludec and glargine. Conclusion: Hospital treatment with degludec‐U100 or glargine‐U100 is equally safe and effective for the management of hyperglycaemia in general medical and surgical patients with type 2 diabetes.